THE ROLE OF GUT MICROBIOTA IN THE PATHOGENESIS OF POLYCYSTIC OVARY SYNDROME - Aleksandra Stępień; Marcelina Podleśna; Kacper Bączek; Karol Chromiak; Kacper Curzytek; Kacper Bluczak; Katarzyna Czechowicz; Julia Radziwiłko; Andżelika Pastuszak; Anna Kozińska (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and aim of the study: Polycystic ovary syndrome (PCOS) is a multifactorial endocrine–metabolic condition affecting a significant proportion of women of reproductive age. Recent scientific evidence suggests that disturbances in gut microbiota composition may play an important role in the metabolic, hormonal and inflammatory abnormalities characteristic of PCOS. The aim of this review was to summarize current knowledge on the relationship between gut microbiota and PCOS, with particular emphasis on pathophysiological mechanisms and potential therapeutic implications.Materials and Methods: This review was conducted through a systematic search of the PubMed database, using keywords related to PCOS, gut microbiota, dysbiosis, insulin resistance and hormonal imbalance. Relevant original research articles were analyzed to identify common mechanisms and clinically meaningful associations.Results: Findings indicate that gut dysbiosis in PCOS is closely linked to increased intestinal permeability, chronic low-grade inflammation, altered short-chain fatty acid (SCFA) production and disturbances in bile acid and tryptophan metabolism. These changes interact with key endocrine pathways regulating insulin sensitivity, androgen excess and estrogen conversion. Recent studies also highlight the therapeutic potential of dietary interventions, probiotics, prebiotics, synbiotics and bioactive nutrients, which can help restore microbial balance and improve metabolic and hormonal outcomes.Conclusions: Understanding the role of the gut microbiota in PCOS pathogenesis opens new perspectives for adjunctive therapeutic strategies. Microbiota-targeted interventions may provide meaningful support alongside conventional treatment, helping to address underlying mechanisms rather than only managing symptoms.